Narcissistic leadership, workplace bullying, turnover intention, and creative performance: a study of nurses - Dalia Khalid Faeq (BMC Nursing)
Abstract Purpose This study aims to develop and propose a research model that investigates the effects of a narcissistic leadership style on nurses. In brief, this empirical study investigates three main aims: (a) direct effect of narcissistic leadership on workplace bullying, nurses turnover intention, and creative performance; (b) effect of bullying on turnover intention and creative performance; and (c) how bullying acts as a mediator between these three variables. Design/methodology/approach The study is a quantitative survey depending on questionnaire, the date were collected from nurses in the private hospitals in Sulaimania city, Kurdistan region of Iraq. Findings The findings from structural equation modeling indicate that workplace bullying acts as a key mechanism linking narcissistic leadership to nurses’ turnover intention and reduced creative performance. Originality/value No empirical study has examined the linkage between narcissistic leadership, workplace bullying, nurses turnover intention and creative performance so far. Moreover, there are few empirical studies in the current literature have tested the mechanism through which workplace bullying is associated with nurses turnover intention and creative performance.